Jaminan Keamanan dan Keselamatan Pengunjung pada Destinasi Wisata - Tjhing, Man lie; Rusmini, Andin; Lestariningsih, Titin (PT. PENERBIT TIGA MUTIARA, 2024)
Over time, engaging in tourism has evolved into a necessity for acquiring delightful experiences. However, such tourism activities also carry inherent risks that can potentially harm visitors. This research, adopting a qualitative approach through a literature study, employs data collection methods by referencing legal documents, pertinent articles, and books relevant to the study. The research findings underscore that legal frameworks guarantee the rights of tourists to protection, safety, and security. Consequently, it is imperative for tourism managers to prioritize the safety of visitors arising from the activities involved. This involves the implementation of robust Standard Operating Procedures (SOP), effective mitigation procedures, optimal functioning of infrastructure, provision of adequate safety equipment, and continuous enhancement of staff competencies. Owners of tourist attractions bear the responsibility of ensuring both the safety and legal protection of visitors, acknowledging the mutual benefits derived from the presence of tourists. Thus, a comprehensive and proactive approach to safety measures is essential in fostering a secure and enjoyable environment for all visitors.